'This Really has the Potential to Destroy us': Jeremy Corbyn's Management of the Problem of Anti‐semitism in the Labour Party. Issue 2 (24th April 2021) - Shaw, Eric
Abstract: During Jeremy Corbyn's period as leader, Labour was convulsed by a row over claims of widespread anti‐semitism in the party, with Corbyn under sustained attack for his alleged complacency—and even connivance. The main purpose of this article is to help explain how the Corbyn leadership managed the 'anti‐semitism crisis'. The first section reviews the sequence of events, the key aspects of the crisis and the various steps taken by the Corbyn leadership. The article then analyses the two sets of factors which drove Corbyn's response. The second section utilises the concept of 'schemas', cognitive shortcuts to shed light on how the leadership framed the problem of alleged endemic anti‐semitism. It argues that the Corbyn leadership's schemas of Israel were integrally linked to those it held on anti‐semitism and played a major role in determining the course of action it took. The third section contends that the Corbyn leadership's decisions and choices were also governed by its approach to party management, in particular by its two central precepts, 'the adversarial frame of reference' and the 'ethic of ultimate ends'. The overall conclusion is that the inadequacy of the Corbyn leadership's schematic understanding of anti‐semitism and of its managerial precepts help explain its failure to resolve the anti‐semitism crisis.